Pesquisa de autoanticorpos contra antígenos intracelulares, em células HEp-2, em Goiânia Goiás - RÊGO, Jozelia (2009)
Autoimmune diseases are a clinical syndrome caused by the activation of T and/or B cells. They are multifactorial in nature and characterized by the presence of autoantibodies directed against cellular components. These autoantibodies can act as diagnostic markers or as predictors for these diseases. The ANA test is a very useful tool in the investigation of autoimmune diseases. OBJECTIVES: a) establishing a correlation between clinical diagnoses and fluorescence patterns in ANA tests on HEp-2 cells; b) determining the frequency of fluorescence patterns; c) establishing a correlation between clinical diagnosis and fluorescence titers; d) establishing possible correlations of changes in fluorescence patterns. CASES AND METHODS: All the ANA requests sent to the Immunorheumatology Laboratory of the Teaching Hospital of the Federal University of Goias, from January / 2000 to December / 2007 were analyzed and those with positive results were selected. For the ANA research, the investigator used the IFI technique and HEp-2 cells as substrate. To classify the fluorescence patterns decision trees proposed by the Brazilian Consensus for Standardization of ANA in HEp-2 cells were used. RESULTS: Among the 8,631 ANA requests, 1,167 presented positive results (13,52%). These positive tests were divided into two groups: Group I (tests requested in one occasion) and Group II (tests requested in more than one occasion). In Group I, nuclear patterns were more prevalent (89,41%). Speckled nuclear patterns were seen more frequently (78,81%), with special notice to fine speckled nuclear patterns (32,74%), coarse speckled nuclear patterns (29,86%) and fine dense speckled nuclear patterns (9,79%). Among the clinical diagnoses, rheumatic autoimmune diseases were the most prevalent (59,87%) and they correlated mostly with speckled nuclear patterns. A positive ANA was noted in 216 cases (34,67%) of non-immune conditions and in 22 cases (3,53%) of undetermined diagnosis. Cases with moderate (1:160) and high (1:640 and > 1:640) titers presented a high association with autoimmune diseases (54,25%; 73,23%; 83,91%, respectively). In Group II, the analytic clinical diagnosis and fluorescence titer factors showed a significant association with the change in the fluorescence pattern. CONCLUSIONS: 1) ANA was found to be positive in autoimmune (61,80%) and in non-autoimmune diseases (34,67%). 2) The most frequently found positive ANA correlation was seen with a diagnosis of lupus erythematosus (38,04%), mainly with coarse speckled nuclear pattern (32,91%), fine speckled nuclear pattern (25,73%), homogeneous nuclear pattern (19,40%) and fine dense speckled nuclear pattern (10,12%). 3) Nuclear patterns were more frequently found (89,41%), and among them, speckled patterns were prevalent (78,81%). 4) Low titers can be found in rheumatic autoimmune diseases and, therefore, can not be interpreted as an exclusion criteria for autoimmune disease, as long as there are clinical indications. 5) High titers can be found in non-autoimmune diseases and, therefore, can not be interpreted as specific to autoimmune diseases. 6) When the ANA test was requested in more than one occasion for the same patient, the clinical diagnosis (especially SLE) and the fluorescence titer (1:40 and 1:160) showed an association with the change of the fluorescence pattern. 7) A correct valuation of the ANA test should associate information from positive results to the clinical history and the physical examination of the patient when they are suggestive of an autoimmune disease, most notably, of rheumatic autoimmune diseases